دور عمليات إدارة المعرفة في تحسين الأداء المؤسسي "دراسة على عينة من أعضاء الهيئة التعليمية " - حسن, طاهر; عيسى, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف البحث إلى التعرف على دور عمليات إدارة المعرفة في تحسين الأداء المؤسسي لدى العاملين في جامعة دمشق، والتعرف على دلالة الفروق في إجابات أفراد عينة البحث على استبيان إدارة المعرفة وفق متغيرات البحث: (المرتبة الاكاديمية، سنوات الخبرة، التوصيف الوظيفي)، وقد اعتمد الباحث على المنهج التحليلي الوصفي، واستخدمت أداة البحث: (استبيان إدارة المعرفة)، حيث شملت عينة البحث (243) عضو هيئة تعليمية في جامعة دمشق. ومن أهم النتائج التي توصل إليها البحث: 1. توجد فروق ذات دلالة إحصائية بين متوسط إجابات أفراد عينة البحث على استبيان إدارة المعرفة وفق متغير المرتبة الاكاديمية لصالح الأفراد الذين يمتلكون رتبة أكاديمية (أستاذ جامعي). 2. توجد فروق ذات دلالة إحصائية بين متوسط إجابات أفراد عينة البحث على استبيان إدارة المعرفة وفق متغير سنوات الخبرة لصالح الأفراد الذين لديهم سنوات خبرة (21 سنة فأكثر). 3. توجد فروق ذات دلالة إحصائية بين متوسط إجابات أفراد عينة البحث على استبيان إدارة المعرفة وفق متغير التوصيف الوظيفي لصالح الأفراد الذين كان توصيفهم الوظيفي (عميد كلية، نائب عميد). وفي ضوء النتائج التِي توصل إليها البحث يقترح الباحث ما يلي: إنشاء بيت خبرة ودعم للقرار في الجامعة من خلال إيجاد قاعدة بيانات ونظم للمعلومات تحدث باستمرار يعمل الجميع في إعدادها، قادرة على تزويد العاملين والإدارات بما تحتاجه من معلومات كمية ونوعية في الوقت المناسب والشكل المناسب، باعتبارها أحد أهم عمليات إدارة المعرفة. ضرورة اخذ الأبعاد الثلاثية الرئيسة للمعرفة : وهي العتاد والبرمجيات والموارد المعرفية بالإضافة إلى العنصر الأهم في هذه المنظومة المتكاملة والذي يعتبر المعادل الموضوعي لموارد النظام المادية وهو الإنسان مولد المعرفة وصانعها..... Research aimed at identifying the role of knowledge management in improving institutional performance of the employees at the University of Damascus, and to identify significant differences in the answers the sample search to identify knowledge management according to variables research: (academic rank, years of experience, job description), has adopted a researcher on the descriptive analytical approach, and used the search tool: (questionnaire knowledge management), where the research sample included 243 teaching faculty member at the University of Damascus. Among the most important findings of the research: There are significant differences between the average Answers members of the research sample to identify knowledge management variable according to academic rank in favor of individuals who have the academic rank of professor. There are significant differences between the average Answers members of the research sample to identify knowledge management variable according to years of experience for the benefit of individuals who have years of experience (21 + years). There are significant differences between the average Answers members of the research sample to identify knowledge management variable according to the job description for the benefit of individuals who had the job description (Dean of the Faculty, Vice-Dean). In light of the research findings ,the researcher proposes the following: 1. Create a house of expertise and decision support at the university through the creation of an constantly updated database and information systems that everyone works in its preparation that provide the employees and departments with the necessary quantitative and qualitative information in the appropriate time and appropriate way, as one of the most important processes of knowledge management. 2. The necessity of taking the three-dimensional key of knowledge: hardware , software, knowledge resources in addition to the human recourses , the knowledge generator and maker and the most important element in this integrated system, which is the substantive equivalent of the physical system.